SIMILAR AND DIFFERENT ASPECTS OF PROVERBS IN RELATION TO OTHER GENRES OF FOLKLORE - Qosimova , Nafisa Farhadovna; Xayriyeva , Ma’mura Fazliddinovna (Innovative Development in Educational Activities, 2023)
This article is dedicated to the the similarities and differences of proverbs with other genres. In examining the mentality of the Uzbek and English people, the Uzbek and English proverbs can highlight the similarities and differences between the two nations. It is possible to find the equivalent proverbs in both on the same topic. In analyzing lingua-cultural aspects of Uzbek and English proverbs, it is important to note that the language and culture of both peoples are interrelated